Blockchain‐driven IoT solutions in agriculture. - Kataev, Mikhail; Bulysheva, Larisa; Krupskiy, Alexander (Systems Research & Behavioral Science)
The Internet of Things (IoT) constitutes a network of physical objects, including devices and systems, capable of intercommunication both among themselves and with external systems via the Internet. Its applications span across various sectors such as manufacturing, medicine, commerce, security, forestry and agriculture. The application of IoT in agriculture involves gathering data from diverse sensors, offering timely and precise solutions. This technology facilitates the reduction of manual labour involved in tasks like animal monitoring, greenhouse management and field surveillance. Integrated sensors within the IoT framework enable the collection of data pertaining to soil, air, water, animal tracking, plant growth and other relevant metrics. Nevertheless, the swift evolution of IoT presents a susceptibility to unauthorized access and compromises in data security. To address this concern, the utilization of blockchain technology has been recommended. This paper proposes a novel IoT architecture integrated with blockchain technology to enhance data security in agricultural applications. A detailed schematic has been devised and implemented in software to illustrate this approach.